Debris and Eutrophication Control for Industrial Environmental Monitoring Using IoT - Subramanian, S; Vinodhini, M (International Journal of Engineering and Technology, 2018)
Pollution is the major concern of all the nations of the world, especially developing countries. From that air pollution and water pollution is due to industrial and automobile exhaust. multitude sensors that can be set in microcontroller. It can be monitoring the water parameters and gas range in industries. This presentation based on not only monitoring the range of ph value and gas range that release from industry and also control the pollution in order to shutdown the power in industry. Â Â